(untitled) (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2025)
In the review named Dimensions of the Meaning of Law, by Dragan Jakovljević, published in issue 25, https://doi.org/10.5937/sinteze13-50082, due to a technical error by the Editorial Board, pointed out by the author of the text, certain parts of the original manuscript were omitted when the text was prepared for publishing. Due to the specificity of the omission, the complete text of the review is published on this occasion. We apologize to the author and readers for the error.